Analyzing High-risk Fertility Behaviors among the Women of Childbearing Age in Bangladesh: Analyzing High-risk Fertility Behaviors among the Women of Childbearing Age in Bangladesh (Dhaka University Journal of Science, 2025)
High-risk-fertility behavior (HRFB) including excessively young or advanced maternal age, narrower birth interval, adhering to higher birth orders, and experiencing an elevated number of live births to a woman often leads to adverse maternal and child health outcomes. The Bangladesh Demographic and Health Survey (BDHS) data was employed to pinpoint the factors motivating high-risk fertility behaviors in women of childbearing age. Pearson’s chi-square test was employed to conduct the unadjusted bivariate association and binary logistic regression model had been implemented to observe the adjusted association between covariates and HRFB. Overall, approximately one-third (31.9%) of women of childbearing age showed risky fertility behaviors. Women’s education, working status, decision-making autonomy, place of residence, husband’s education, husband’s age, media exposure, and violence against women were significant predictors of maternal HRFB. The escalating prevalence of HRFB in Bangladesh is a cause for concern. Policymakers should prioritize initiatives such as enhancing parental education, fostering women's autonomy, and implementing knowledge- based healthcare interventions for women. These measures aim to mitigate risky fertility behaviors and contribute to improved reproductive health outcomes.Dhaka Univ. J. Sci. 73(2): 127-134, 2025 (July)